Profiles of cognitive impairment in chronic heart failure—A cluster analytic approach - Göpfert, Dennis; Traub, Jan; Sell, Roxane; Homola, György A.; Vogt, Marius; Pham, Mirko; Frantz, Stefan; Störk, Stefan; Stoll, Guido; Frey, Anna (Frontiers in Human Neuroscience, 2023)
Background: Cognitive impairment is a major comorbidity in patients with chronic heart failure (HF) with a wide range of phenotypes. Here, we aimed to identify and compare different clusters of cognitive deficits. Methods: The prospective cohort study “Cognition.Matters-HF” recruited 147 chronic HF patients (aged 64.5±10.8 years; 16.2% female) of any aetiology. All patients underwent extensive neuropsychological testing. We performed hierarchical cluster analysis of the cognitive domains intensity of attention, visual/verbal memory and executive function. Generated clusters were compared exploratively with respect to the results of cardiological, neurological and neuroradiological examinations without correction for multiple testing. Results: Dendrogram and the scree plot suggested three distinct cognitive profiles: In the first cluster, 42 patients (28.6%) performed without any deficits in all domains. Exclusively intensity of attention deficits were seen in the second cluster including 55 patients (37.4%). A third cluster with 50 patients (34.0%) was characterized by deficits in all cognitive domains. Age (p=0.163) and typical clinical markers of chronic HF such as ejection fraction (p=0.222), 6-minute walking test distance (p=0.138), NT-proBNP (p=0.364) and New York Heart Association class (p=0.868) did not differ between clusters. However, we observed that women (p=0.012) and patients with previous cardiac valve surgery (p=0.005) prevailed in the “global deficits” cluster and the "no deficits" group had a lower prevalence of underlying arterial hypertension (p=0.029). Total brain volume (p=0.017) was smaller in the global deficit cluster and serum levels of glial fibrillary acidic protein were increased (p=0.048). Conclusions: Apart from cognitively healthy and globally impaired HF patients, we identified a group with deficits only in intensity of attention. Women and patients with previous cardiac valve surgery are at risk for global cognitive impairment when suffering HF and could benefit from special multimodal treatment addressing the psychosocial condition.